Dorsal Wrist Pain in the Extended Wrist-Loading Position: An MRI Study - Nance, Erin M.; Byun, David J.; Endo, Yoshimi; Wolfe, Scott W.; Lee, Steve K. (Journal of Wrist Surgery, 2017)
Background The etiology of dorsal wrist pain associated with loading of the wrist in extension has not been clearly identified in the literature.Purpose Many exercise disciplines incorporate upper extremity weight-bearing exercises in an extended wrist posture, for example push-ups, plank position, and various yoga and Pilates poses. This study evaluates patients with dorsal wrist pain in the extended wrist-loading position and identifies anatomic abnormalities in the wrist using magnetic resonance imaging (MRI).Methods A retrospective chart review was performed comparing MRI of patients who complained of dorsal wrist pain while performing weight bearing in a wrist extension position with a control group of patients who complained of ulnar-sided wrist pain. The primary MRI outcome was dorsal wrist pathology, including occult dorsal ganglion cyst, scapholunate ligament tear or degeneration, and dorsal capsulitis.Results Dorsal wrist pathology was significantly more prevalent in patients with dorsal wrist pain (84%) than in the patient cohort with ulnar-sided wrist pain (12%). Occult dorsal ganglion cysts were the most common sources of pathology (76%).Conclusion MRI demonstrated an identifiable dorsal abnormality in 84% of patients with dorsal wrist pain associated with weight bearing on the extended wrist. Occult dorsal ganglion cysts are the most common cause of dorsal wrist pain, followed by partial scapholunate tears. When patients complain of dorsal wrist pain during specific extended loading wrist positions such as push-ups, yoga, or Pilates poses, an MRI may be warranted to help identify anatomic abnormalities that may help guide treatment choices.Level of Evidence Diagnostic, Level III.
Keywords: dorsal wrist pain; wrist loading; dorsal ganglion; imaging